Assessing the environmental risks of sulfonylurea pollutants: Insights into the risk priority and structure-toxicity relationships - Zhi-Cong He; Tao Zhang; Xin-Fang Lu; Rui Li; Wei Peng; Fei Ding (Ecotoxicology and Environmental Safety)
Sulfonylureas are widely used herbicides globally; however, the health risks associated with exposure to these compounds are poorly understood. This study used fuzzy clustering to categorize 44 sulfonylurea compounds into three risk priority levels (I, II, and III) and further investigated their structure-toxicity relationships. The order of the risk priority levels was level I＜level II＜level III. The pecking order of protein affinity was on the order of 104 M−1, which was consistent with the order of the risk priority levels. Moreover, toxic conjugations induced significant changes in protein conformation, with high-risk sulfonylurea causing substantial conformational changes. Given that the conformations of sulfonylurea within the reactive domain were highly similar, the patterns of toxic actions were considerably similar as well. Structure-toxicity relationship analysis indicated a positive correlation among Gibbs free energy change (ΔG°), affinity between sulfonylurea and protein, logarithm of the octanol-water partition coefficient (logKow), and risk priority. Specifically, a higher ΔG° value corresponded to stronger affinity, and a higher logKow value corresponded to a higher environment risk. The electronegativity of the aromatic ring on the left side of the sulfonylurea molecule is a key determinant influencing affinity - higher electronegativity of this aromatic ring weakened the affinity of sulfonylurea for protein and reduced the risk. When the aromatic ring on the left side of sulfonylurea was consistent, an increase in the electronegativity of the heterocyclic ring on the right side resulted in a stronger affinity for protein and an increased risk. This study provides a mechanistic foundation for evaluating the health risks associated with exposure to sulfonylurea.